PECULIARITIES OF MOTIVATION DEVELOPMENT FOR ACHIEVING SUCCESS AMONG STUDENTS OF AZERBAIJAN - Кулієва-Кабаоглу, Шенай; Сорока, Анатолій Володимирович (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2018)
The article is devoted to the study of achievement motivation features as well as a personality characteristics of Azerbaijani students interconnected with it. The research sample consisted of 63 students of 1-4 courses of Social Sciences and Psychology Faculties at the Baku State University, specializing in «Social Work». The results of the research show that in the process of teaching students the number of students with a low motivation for achieving success increases and there is a decrease in the expressiveness of the motive for avoiding failure. In the process of training, the level of claims is relatively optimized, and the students of the fourth course have a decrease in the level of academic achievement, we explain this as the personal characteristics of the subjects of this course. Such personality traits revealed: low self-esteem, insuffiiently formed motive for success, as well as diffiulties in fiding employment for graduates on their specialty